IGEPAC-Bela Vista e o tombamento do Teatro Oficina: Representação, governo e contestação no Bixiga - Dirceu Cadena (Confins)
This work aims to discuss the production of the representation of Bixiga in the General Inventory of Environmental, Cultural and Urban Heritage of São Paulo-Bela Vista (IGEPAC-Bela Vista). It is considered that contemporary political geography can be analyzed based on representations, government decisions and protest movements, aspects analyzed at Bixiga within the framework of heritage policy. The analysis of the documents produced to demand the classification of the Teatro Oficina as heritage or the request for the creation of a public park in the land adjacent to the building will show that the group associated with the theatre has mobilized various existing laws on heritage to challenge the governments decisions and build new representations for the neighbourhood.